Evaluation of the wing cell contour to distinguish between Stomoxys bengalensis and Stomoxys sitiens (Diptera: Muscidae) using outline-based morphometrics - Thekhawet Weluwanarak; Tanawat Chaiphongpachara; Tanasak Changbunjong (Current Research in Parasitology and Vector-Borne Diseases)
The blood-sucking flies of the genus Stomoxys Geoffroy, 1762 (Diptera: Muscidae) are significant ectoparasites that can cause irritation and transmit pathogens to both animals and humans. Within the genus Stomoxys, two species, Stomoxys bengalensis and Stomoxys sitiens, have similar morphology and coexist in the same habitat. Accurate species identification of these flies is crucial for understanding disease vectors and implementing effective control measures. In this study, we assessed the effectiveness of outline-based geometric morphometrics (GM) by analyzing the wing cell contour of the first posterior cell (R5) to distinguish between species and sexes of S. bengalensis and S. sitiens. Our results demonstrate that the outline-based GM method is highly effective in distinguishing between species and sexes of these flies based on contour shape, with accuracy scores ranging from 90.0% to 97.5%. Therefore, outline-based GM emerges as a promising alternative to landmark-based GM or as a supplementary tool in conjunction with traditional morphology-based methods for species identification.